Repurposing Probenecid to Inhibit SARS-CoV-2, Influenza Virus, and Respiratory Syncytial Virus (RSV) Replication - Ralph A. Tripp; David E. Martin (Viruses, 2022)
Viral replication and transmissibility are the principal causes of endemic and pandemic disease threats. There remains a need for broad-spectrum antiviral agents. The most common respiratory viruses are endemic agents such as coronaviruses, respiratory syncytial viruses, and influenza viruses. Although vaccines are available for SARS-CoV-2 and some influenza viruses, there is a paucity of effective antiviral drugs, while for RSV there is no vaccine available, and therapeutic treatments are very limited. We have previously shown that probenecid is safe and effective in limiting influenza A virus replication and SARS-CoV-2 replication, along with strong evidence showing inhibition of RSV replication in vitro and in vivo. This review article will describe the antiviral activity profile of probenecid against these three viruses.